POTOMETRIUM (POT TANAMAN GEOMETRIS DAN TERARIUM) SERTA PEMASARAN DIGITAL BAGI KELOMPOK PENJUAL TANAMAN HIAS DI KELURAHAN MACCINI SOMBALA KOTA MAKASSAR - Citra Amalia Amal; Andi Annisa Amalia; Sri Andayaningsih (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
POTOMETRIUM (Geometric and Terraium Pot Plants) and Digital Marketing for The Ornamental Plant Traders Group in Maccini Sombala Village, Makassar CityAbstract. The world of architecture is currently colored by the development of farming methods for urbanites in limited land by arranging plants into special containers of high artistic value such as terrariums and pots in the style of industrial geometry. Some of the problems faced by ornamental plant sellers are the high competition in selling similar types of potted plants because the types of pots sold are generally the same as those on the market, not yet skilled in assembling cactus and succulent plants into terrarium containers, and the sales system is still conventional in nature. To overcome these problems, community service was carried out in the form of developing productive partners with the theme POTOMETRIUM (Geometry and Terrarium Plant Pots). POTMETRIUM PPM activities consist of preparatory activities, identification and classification of ornamental plant sales groups, dissemination of POTOMETRIUM product knowledge and socialization of PKM implementation activities, implementation of geometric pot making workshops, implementation of technical terrarium arranging workshops, implementation of digital marketing technical workshops, making video tutorials POTOMETRIUM, publications implementation of activities, preparation of activity reports, and implementation of monitoring and evaluation of the results of PKM activities.Keywords: Geometric, terrarium, product, digital, ornamental plant.Abstrak. Dunia arsitektur saat ini diwarnai perkembangan metode bercocok tanam bagi kaum urban di lahan terbatas  dengan merangkai tanaman ke dalam wadah khusus yang bernilai seni tinggi diantaranya Terarium dan Pot bergaya industrial geometri. Beberapa permasalahan yang dihadapi oleh kelompok penjual tanaman hias yaitu tingginya persaingan penjualan jenis pot tanaman sejenis karena jenis pot yang dijual umumnya sama dengan yang ada di pasaran, belum terampil dalam merangkai tanaman kaktus dan sukulen ke dalam wadah terarium, dan sistem penjualan masih bersifat konvensional. Untuk mengatasi permasalahan tersebut, maka dilakukan pengabdian kepada masyarakat dalam bentuk pengembangan mitra produktif ber-tema POTOMETRIUM (Pot Tanaman Geometri dan Terarium). Kegiatan PPM POTOMETRIUM terdiri atas kegiatan persiapan, identifikasi dan klasifikasi kelompok penjual tanaman hias, sosialisasi pengetahuan produk POTOMETRIUM dan sosialisasi pelaksanaan kegiatan PKM, pelaksanaan workshop pembuatan pot geometris, pelaksanaan workshop teknis merangkai terarium, pelaksanaan workshop teknis pemasaran digital, pembuatan video tutorial POTOMETRIUM, publikasi pelaksanaan kegiatan, penyusunan laporan kegiatan, dan pelaksanaan monitoring serta evaluasi hasil kegiatan PKM.Kata Kunci: Geometris, terarium, produk, digital marketing, tanaman hias.